Effect of cAMP Receptor Protein Gene on Growth Characteristics and Stress Resistance of Haemophilus parasuis Serovar 5 - Jiang, Changsheng; Cheng, Yufang; Cao, Hua; Zhang, Bingzhou; Li, Jing; Zhu, Ling; Li, Zhonghua; Zeng, Wei; Li, Chang; He, Qigai (Frontiers in Cellular and Infection Microbiology, 2020)
Haemophilus parasuis (HPS), a member of the family Pasteurellaceae, is a common bacteria in the upper respiratory tract of pigs but under certain circumstances can cause serious systemic disease (Glasser's disease) characterized by severe infection of the upper respiratory tract, fibrinous polyserositis, polyarthritis, and meningitis. cAMP receptor protein (CRP) is among the most important global regulators, playing a vital role in adapting to environmental changes during the process of bacterial infection. In order to investigate the function of the crp gene in the growth characteristics of H. parasuis serovar 5 (HPS5) and its ability to overcome adverse environmental stresses, a crp mutant strain (Δcrp) was constructed and verified. In this study, we found that the crp gene was involved in growth rate, biofilm formation, stress tolerance, serum resistance, and iron utilization. Compared with the wild type, both the growth rate of the crp mutant and its resistance to osmotic pressure decreased significantly. Similar phenomena were also found in biofilm formation and iron utilization. However, the resistance to heat shock and serum complement of the crp mutant were enhanced. This study aimed to reveal the function in growth characteristics and stress resistance of the crp gene in HPS5. Whether it relates to virulence requires additional in-depth research.